DIAGNOSING CASES OF COMPLICATED APPENDICITIS USING NEUTROPHIL-LYMPHOCYTE RATIO: A PROSPECTIVE STUDY - SHAIKH, SN; ZAHEER, F; KHAN, H; MAQBOOL, N; SHEIKH, K; SHAIKH, S (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to investigate the significance of the neutrophil-lymphocyte ratio (NLR) in the diagnosis of complicated appendicitis and distinguish it from uncomplicated appendicitis. Acute appendicitis is a typical surgical emergency, with a lifetime probability of 8.6% for males and 6.7% for females. It is crucial to diagnose and treat this condition promptly to prevent complications such as perforation, peritonitis, and fluid collection, which can lead to extended hospital stays, morbidity, and mortality. The prospective observational study lasted for three months at Ruth K.M. Pfau Civil Hospital, Karachi. Patients between the ages of 16 and 40 who were diagnosed with acute appendicitis using clinical and/or radiological evidence and underwent appendectomy were included in the study. Pre-operative assessments and laboratory results, including NLR, were recorded and compared to operative findings. The study found that NLR values greater than 8.0 were indicative of complicated appendicitis, with a sensitivity of 90.9% and a specificity of 100%. Therefore, NLR has a high predictive value for identifying complicated appendicitis in our local population.